Empowering Farmer Groups in Ponggok District, Blitar Regency in the Creative Economy Era with Digital Marketing - Reza Anggapratama; Dwi Irnawati; Danang Ananda Yudha; Azhari Azhari (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The creative economy plays a vital role in business growth and economic growth. The rapid growth of the internet results from technological advances in today's digital era. One strategy to overcome competition and boost income is to empower farmer groups with digital marketing in the creative economy era. The farmer group in Ponggok District, Blitar Regency, is one of them. Farmer groups in Ponggok District process waste from coconut shells often found in Ponggok District Blitar Regency. Natural pesticides or biopesticides (BIOPEST) can be made from coconut shells processed by Ponggok District, Blitar Regency farmer groups. Digital marketing and education in the creative economy are discussed in this report. This did because the farmer groups in Ponggok District, Blitar Regency, still needed to understand. As a result, this activity aims to educate farmer groups on how to market digitally in the future. This activity focuses on developing quality capabilities to face business competition in the creative economy sector by using digital marketing, such as packaging, adding economic value, becoming a commodity, and managing a business.